2013
DOI: 10.5037/jomr.2013.4305
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Midazolam May Prevent Gagging Reflex: a Case Report

Abstract: BackgroundGagging can become a conditioned response that makes dental treatment difficult or impossible for both the individual and the dentist. The aim of this study is to report a 50 year old female and two children (15 and 11 years old) with exaggerated gag reflex referred to Faculty of Dentistry of Selçuk University.MethodsDuring obtaining records, taking impression procedure was elicited the patients’ hypersensitive gagging reflex. Therefore, it was decided to administer intranasal midazolam to facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In children with an intense gagging reflex, procedures such as radiological examinations may not be completed, making it harder to arrive at the correct diagnosis. Further, difficulties in taking maxillary impressions may prevent other children from undergoing orthodontic treatment or wearing (prosthetic) removable appliances 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…In children with an intense gagging reflex, procedures such as radiological examinations may not be completed, making it harder to arrive at the correct diagnosis. Further, difficulties in taking maxillary impressions may prevent other children from undergoing orthodontic treatment or wearing (prosthetic) removable appliances 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Relaxation techniques [22,23] and even diverting attention [24] can also ameliorate gagging. A case report found that intranasal midazolam, a benzodiazepine, reduced the patient's experience of the gag reflex [25]. Additionally, some case reports show that using chemical stimulation of the oral palate with a sodium chloride solution can temporarily reduce the gag reflex [26][27][28], although a controlled study failed to find a significant effect of table salt in reducing the gag reflex [13].…”
Section: Predictive Gagging Survey Gagging Severity Indexmentioning
confidence: 99%
“…8.2% of dutch adults stated that they generally gagged during dental treatment (van Houtem et al, 2015) and who were primarily seeking emergency dental care stated that 49% of them gagged sometimes or frequently at the site of a dentist, whereas an additional 7.5% of adults stated that they almost always gagged (Randall et al, 2014). Knowledge of an individual's likelihood to gag is highly essential and of particular importance to the pediatric dentists as prior information of gagging problem in children can help clinicians to deliver treatment effectively with appropriate use of behavioural management techniques (Malkoc et al, 2013;Sari and Sari, 2010).…”
Section: Introductionmentioning
confidence: 99%